The Role of Departments for Juvenile Affairs of Internal Affairs Bodies in the Prevention of Delinquent Behavior of Minors: History and Modernity - N. I. Pishikina (Теоретическая и прикладная юриспруденция)
The article is devoted to the study of the activities of a specialized subject for the prevention of delinquent behavior of minors in the system of internal affairs bodies, today called the juvenile department. The historical aspect of the creation and reformation of this subject, the problems of activity at the present stage are analyzed. On the basis of the study, an assumption is made about the illegality of certain powers of this unit, as well as about the unreasonable expansion of functions and powers at the present time, which affects the quality of preventive activities.